ANALISIS KONSENTRASI LOGAM BERAT TIMBAL (Pb) DAN KADMIUM (Cd) PADA ECENG GONDOK (Eichhornia crassipes) DI PERAIRAN SUNGAI INDRAGIRI SEBAGAI RANCANGAN MODUL KONSEP PENCEMARAN LINGKUNGAN DI SMA - Hidayat, Dimas Bayu; Febrita, Elya; ', Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research was conducted to find out the concentration of heavy metal Lead (Pb) and Cadmium (Cd) at water hyacinth (Eichhornia crassipes) in Indragiri River Watershed Indragiri Hilir Regency as the biology module design of environmental pollution concept in Senior High School (SMA) conducted in May-July 2016. The research station is conducted by purposive random sampling taking into account the environmental conditions based on community activity around the river and the existence of Eichhornia crassipes. The main parameters in this study include concentrations of heavy metals Pb and Cd in river water, sediment and Eichhornia crassipes, and physical-chemical parameters as supporting parameters. The results showed that the average concentration of Pb heavy metals in river water was 0.276 ppm and Cd 0.126 ppm. The average concentration of Pb heavy metals in sediments was 4.61 ppm and Cd 0.75 ppm. The accumulation of heavy metals Pb and Cd Eichhornia crassipes are included in the low category, ie the average concentration of Pb heavy metals in root organs 3.02 ppm, on leaf organ 2.61 ppm, and in leaf organ 2.09 ppm. While the concentration of heavy metal Cd on root organs 0.47 ppm, on the leaf organ 0.39 ppm, and the leaf organ 0.362 ppm. Then, research results of heavy metal concentrations of Pb and Cd in river water, sediment, and Eichhornia crassipes that have been implemented will serve as a source in the preparation of learning modules in high school.Keywords: Biology Module, Eichhornia crassipes, Heavy Metals Pb and Cd, Water Pollution